Flooded development, democracy, and Brazil's Belo Monte Dam - Klein, Peter Taylor (Nature, society, and culture., 2022)
"Contemporary dam construction is markedly different from what it was in the middle of the twentieth century, when governments ignored the negative impacts of large-scale infrastructure projects. In recent decades, many democratic countries have continued to use dams to promote growth, but have also introduced accompanying programs to alleviate the harmful consequences of dams for local people, reduce poverty, and promote participatory governance. This type of dam building undoubtedly represents a step forward in responsible governing. But have these policies really worked? Flooded provides insights into the little-known effects of these approaches through a close examination of Brazil's Belo Monte hydroelectric facility. After a remarkable three decades of controversy over damming the Xingu River, a tributary of the Amazon, the dam came to fruition under the left-of-center Workers' Party and became the world's fourth largest dam when it was completed in 2019. Billions of dollars for social welfare programs accompanied construction. Nonetheless, the dam brought extensive social, political, and environmental upheaval to the region. The population soared, cost of living skyrocketed, violence spiked, pollution increased, and already overextended education and healthcare systems were strained. Nearly 40,000 people were displaced and ecosystems were significantly disrupted. Klein tells the stories of dam-affected communities, including activists, social movements, non-governmental organizations, and public defenders and public prosecutors. He details how these groups, as well as government officials and representatives from private companies, negotiated the upheaval through protests, participating in public forums for deliberation, using legal mechanisms to push for protections for the most vulnerable, and engaging in myriad other civic spaces. This ground-level perspective shows how local democracy is at once strengthened and weakened by a rapid influx of government resources. The introduction of funding and opportunities divided dam resistance and split previously unified social and political networks, yet it also allowed for deliberative processes to emerge. More people participated in civic life and some dam-affected communities achieved victories in their struggles for compensation. Yet the local democracy that state and civil society actors produced was insufficient and costly for many participants, and still others were simply excluded. Even when marginalized groups managed to make gains, they did so despite, rather than because of, the conditions. A twisted form of democratic deepening emerged - but the only kind that was possible for local people and their advocates to create. Flooded provides a rich ethnographic account of democracy and development in the making. In the midst of today's climate crisis, this book showcases the challenges and opportunities of meeting increasing demands for energy in equitable ways"-- Provided by publisher.